The risk of pig and chicken farming for carriage and transmission of Escherichia coli containing extended-spectrum beta-lactamase (ESBL) and mobile colistin resistance (mcr) genes in Thailand. Issue 3 (23rd March 2023) - Sudatip, Duangdao; Mostacci, Nadezda; Tiengrim, Surapee; Thamlikitkul, Visanu; Chasiri, Kittipong; Kritiyakan, Anamika; Phanprasit, Wantanee; Thinphovong, Chuanphot; Abdallah, Rim; Baron, Sophie Alexandra; Rolain, Jean-Marc; Morand, Serge; et al.
Abstract : South-East Asian countries report a high prevalence of extended-spectrum cephalosporin- (ESC-) and colistin-resistant Escherichia coli (Col-R- Ec ). However, there are still few studies describing the molecular mechanisms and transmission dynamics of ESC-R- Ec and, especially, Col-R- Ec . This study aimed to evaluate the prevalence and transmission dynamics of Ec containing extended spectrum beta-lactamases (ESBL) and mobile colistin resistance ( mcr ) genes using a 'One Health' design in Thailand. The ESC-R- Ec and Col-R- Ec isolates of human stool samples (69 pig farmers, 155 chicken farmers, and 61 non-farmers), rectal swabs from animals (269 pigs and 318 chickens), and the intestinal contents of 196 rodents were investigated. Resistance mechanisms and transmission dynamics of Ec isolates ( n =638) were studied using short and long read sequencing. We found higher rates of ESBL- Ec isolates among pig farmers ( n =36; 52.2%) than among chicken farmers ( n =58; 37.4 %; P <0.05) and the control group ( n =61; 31.1 %; P <0.05). Ec with co-occurring ESBL and mcr genes were found in 17 (6.0 %), 50 (18.6 %) and 15 (4.7 %) samples from humans, pigs and chickens, respectively. We also identified 39 (13.7 %) human samples with non-identical Ec containing ESBL and mcr . We found higher rates of ESBL- Ec, in particular CTX-M-55, isolates among pig farmers than among non-pig farmers ( P <0.01). 'Clonal' animal-human transmission of ESBL- Ec and Ec with mcr genes was identified but rare as we overall found a heterogenous population structure of Ec . The Col-R- Ec from human and animal samples often carried mcr -1.1 on conjugative IncX4 plasmids. The latter has been identified in Ec of many different clonal backgrounds.